2019
DOI: 10.1152/jn.00240.2019
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous action potentials in retinal horizontal cells of goldfish (Carassius auratus) are dependent upon L-type Ca2+ channels and ryanodine receptors

Abstract: Horizontal cells (HCs) are interneurons of the outer retina that undergo graded changes in membrane potential during the light response and provide feedback to photoreceptors. We characterized spontaneous Ca2+-based action potentials (APs) in isolated goldfish ( Carassius auratus) HCs with electrophysiological and intracellular imaging techniques. Transient changes in intracellular Ca2+ concentration ([Ca2+]i) were observed with fura-2 and were abolished by removal of extracellular Ca2+ or by inhibition of Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…Additionally, GABA-positive cells comprised 41.1% (56/136) of all fixed cells observed, which is in line with reports that H1 is the most common subtype in fish (e.g., Ariel, Lasater, Mangel, & Dowling, 1984;Young & Dowling, 1984). Verification of other HC subtypes within HCs of teleosts (e.g., goldfish, carp, catfish) and skates are known to exhibit Ca 2+ -dependent APs (Country et al, 2019;Johnston & Lam, 1981;Lasater et al, 1984;Murakami & Takahashi, 1987;Tachibana, 1981). In many reports, the APs occurred spontaneously (Country et al, 2019), especially in the presence of Ba 2+ or K + channel blockers (Murakami & Takahashi, 1987;Tachibana, 1981).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, GABA-positive cells comprised 41.1% (56/136) of all fixed cells observed, which is in line with reports that H1 is the most common subtype in fish (e.g., Ariel, Lasater, Mangel, & Dowling, 1984;Young & Dowling, 1984). Verification of other HC subtypes within HCs of teleosts (e.g., goldfish, carp, catfish) and skates are known to exhibit Ca 2+ -dependent APs (Country et al, 2019;Johnston & Lam, 1981;Lasater et al, 1984;Murakami & Takahashi, 1987;Tachibana, 1981). In many reports, the APs occurred spontaneously (Country et al, 2019), especially in the presence of Ba 2+ or K + channel blockers (Murakami & Takahashi, 1987;Tachibana, 1981).…”
Section: Discussionsupporting
confidence: 89%
“…Significant positive correlations were found for AUC (r 2 = .059, p < .01) and duration (r 2 = .043, p < .05); frequency was negatively correlated with r d/s (r 2 = .047, p < .01). No significant correlations were found for amplitude, TTP, or baseline recently, spontaneous, all-or-nothing Ca 2+ transients were found in goldfish in Ca 2+ imaging experiments (Country et al, 2019;Kreitzer et al, 2012). These transients represent APs, and involve Ca 2+ influx into the cytosol via L-type Ca 2+ channels and ryanodine receptors (Country et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Cells were treated with dantrolene to exclude the effects of RyR, another major Ca 2+ pathway in ER/SR, to identify the mechanism involving the PLC/IP 3 Ca 2+ pathway of CL or LMA. Dantrolene suppression of RyR increased [Ca 2+ ] c. Furthermore, dantrolene treatment of goldfish retinal neuron cells abolished Ca 2+ transients and increased baseline Ca 2+ levels, whereas concurrent treatment with dantrolene and nifedipine suppressed the dantrolene-induced increase in baseline Ca 2+ , suggesting that this increased Ca 2+ was introduced into cells through L-type Ca 2+ channels [34]. The present study showed that simultaneous treatment with dantrolene and CL resulted in a greater increase in [Ca 2+ ] c than treatment with dantrolene alone, suggesting that the CL-or LMA-induced increase in Ca 2+ was introduced through a pathway other than L-type Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 96%